Virtual Desktop Infrastructure Sebagai Pendukung Perkuliahan Dengan Algoritma Virtual Machine - dicopran sisco dico; Tata Sutabri (PPPM Institut Teknologi Pagar Alam, 2025)
The use of mobile computing devices has become a trend among students, many students who have it and used it in everyday activities. However, these devices are still limited in its use and, rarely used to assist students in college activities. Virtual desktop infrastructure is a solution, so that mobile devices owned by students can be used in lectures. VDI allows students to run applications that previously could only run on personal computers with Microsoft Windows operating system, so it can run on any device they own. This paper will describe testing of the maximum number of virtual desktops that can run on hardware that is already available, and the performance of the server when running the maximum number of virtual desktops.